Deficits in ascending pain modulation pathways in breast cancer survivors with chronic neuropathic pain: A resting-state fMRI study - Liu, Rui; Qiao, Na; Shi, Shuwei; Li, Suyao; Wang, Yingman; Song, Jie; Jia, Wenting (Frontiers in Neurology, 2022)
Purpose Breast cancer (BC) is the highest frequent malignancy in women globally. Approximately 25–60% of BC patients with chronic neuropathic pain (CNP) result from advances in treating BC. Since the CNP mechanism is unclear, the various treatment methods for CNP are limited. We aimed to explore the brain alternations in BC patients with CNP and the relationship between depression and CNP utilizing resting-state functional magnetic resonance imaging (rs-fMRI). Methods To collect the data, the female BC survivors with CNP (n = 20) and healthy controls (n = 20) underwent rs-fMRI. We calculated and compared the functional connectivity (FC) between the two groups using the thalamus and periaqueductal gray (PAG) as seed regions. Results Patients with BC showed increased depression and FC between the thalamus and primary somatosensory cortices (SI). Moreover, the Hospital Anxiety and Depression Scale-Depression (HADS-D) and pain duration were linked positively to the strength of FC from the thalamus to the SI. Furthermore, the thalamus-SI FC mediated the impact of pain duration on HADS-D. Conclusion In BC patients with CNP, the ascending pain regulation mechanism is impaired and strongly associated with chronic pain and accompanying depression. This research increased our knowledge of the pathophysiology of CNP in patients with BC, which will aid in determining the optimal therapeutic strategy for those patients.